2017
DOI: 10.3892/ol.2017.5784
|View full text |Cite
|
Sign up to set email alerts
|

WT1-associated protein is a novel prognostic factor in pancreatic ductal adenocarcinoma

Abstract: Although Wilms tumor 1 (WT1)-associated protein (WTAP) was initially found to be a specific WT1-binding protein, it has increasingly attracted attention because of its oncogenic role in various types of malignancies, including cholangiocarcinoma, glioblastoma and acute myeloid leukemia. However, the clinical impact of WTAP on pancreatic ductal adenocarcinoma (PDAC) is still unknown. A total of 145 patients who underwent surgical treatment from 2004 to 2008 were enrolled in the present study. The cytoplasmic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 61 publications
4
50
1
Order By: Relevance
“…The results of the present study, to the best of our knowledge, are the first to suggest that strong immunostaining of WT1 in the PDA cytoplasm may be a potentially useful marker to predict the risk of relapse and progression in patients with PDA. Recently, it was reported that the overexpression of WT1-associated protein (WTAP), a ubiquitously expressed nuclear protein, reduced the OS time of PDA patients via a WTAP-WT1 axis (49). This study supports the present findings that cytoplasmic WT1 overexpression in PDA is associated with a worse prognosis.…”
Section: Wt1 Intensity ----------------------------------------------supporting
confidence: 91%
“…The results of the present study, to the best of our knowledge, are the first to suggest that strong immunostaining of WT1 in the PDA cytoplasm may be a potentially useful marker to predict the risk of relapse and progression in patients with PDA. Recently, it was reported that the overexpression of WT1-associated protein (WTAP), a ubiquitously expressed nuclear protein, reduced the OS time of PDA patients via a WTAP-WT1 axis (49). This study supports the present findings that cytoplasmic WT1 overexpression in PDA is associated with a worse prognosis.…”
Section: Wt1 Intensity ----------------------------------------------supporting
confidence: 91%
“…Recently, more and more studies have suggested that the abnormal expression of the m 6 A RNA methylation regulators is involved in human cancer. The writer WTAP was reported to be a oncogene in different cancers, such as AML (38), glioblastoma (39), and pancreatic ductal adenocarcinoma (40). The eraser ALKBH5 was observed to be up regulated in glioblastoma stemlike cell (GSCs), leading to the initiation and development of glioblastoma (41).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, more recent studies have shown that the nuclear expression of WT1 in pancreatic ductal adenocarcinoma correlates with gender and tumor stage, while cytoplasmic staining correlates with gender, histological grade and perineural invasion. In addition, the same authors reported that a high nuclear expression of WT1 in pancreatic tumor tissues was significantly associated with poor overall survival, suggesting a possible role for it as a molecular biomarker of a poor prognosis among patients with pancreatic ductal adenocarcinoma [109].…”
Section: Wt1 Expression In Pancreatic Ductal Adenocarcinomasmentioning
confidence: 96%